Comparative study of the possibility of generalization of specific remedies in International documents to Iranian law - Mohammad Mahdi Masoumi (مطالعات فقه و حقوق اسلامی, 2024)
In domestic law, some forms of remedies for breach of contractual obligations, such as the obligation to execute a commitment, termination of a contract and claim for damages, are in common with what is stated in international documents. However, some of the practices in these documents are not in Iranian law and are specific. Such as judicial penalty, interest payments, price Reduction, and resale of goods. Given the progress and dramatic increase in contractual relationships amongst the community, strengthening domestic rights in this field seems necessary. International documents contain regulations on remedies that, in quantitative and qualitative terms, allow for fair and complete compensation for damage. Therefore, their generalization to domestic law will provide the objective of realization of liability, the full compensation of damages, as appropriate. However, it is not possible to pay legal interest in domestic law, but predicting other international remedies will strengthen Iranian law in this regard.